Parental Knowledge and Personal Hygiene Practices Associated with Stunting Incidence in Children 24-60 Months Old in Mlarak Village - Miftakhur Rohmah; Arini (Master of Public Health Program Universitas STRADA Indonesia, 2023)
Stunting is a major nutritional problem worldwide. Stunting is caused by several interrelated factors such as parental knowledge about hygiene and personal hygiene practices. This study used an observational analytic design and a cross sectional design. The sampling technique used to take a sample of 68 mothers and children is purposive sampling. The independent variable of knowledge and practice of personal hygiene was taken using a questionnaire instrument while the dependent variable of stunting was observed directly during the study. The results showed that most of the mothers (58.8%) had good knowledge about hygiene, most of the toddlers (76.5%) practiced good personal hygiene; and 13 children (19.1%) were stunted. There is a correlation between parents' knowledge about hygiene (p-value:0.004) and the practice of personal hygiene (p-value (0.032) with the incidence of stunting. Stunting prevention efforts are to improve communication between health workers and the community through the development of IEC messages that are tailored to the needs of the target group, namely Households, 1,000 HPK, WUS, and young women. Various communication channels such as posyandu, parenting classes, classes for pregnant women, to adolescent reproductive counseling.